2014
DOI: 10.17338/trainology.3.1_6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of strength training on isometric force production symmetry in recreationally trained males

Abstract: Objectives:The purpose of this investigation was to determine what effect a bilateral strength training regimen has on isometric force production symmetry and if changes in force production symmetry can be accounted for by differences in pre-intervention strength levels. Design: Sixteen recreationally trained males (1-RM squat: 146.8 ± 23.0 kg.) were assigned to two groups for the 7-week training intervention: strong (S) and weak (W) based on pre-training squat isometric peak force allometrically scaled (IPFa)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 18 publications
1
44
2
Order By: Relevance
“…Between-group analyses also indicated a 'large' and significant difference between median-split fast and slow performers. Whilst previous investigations have associated asymmetries in force-related parameters with impaired athletic performance (Bailey et al, 2013;Bailey et al, 2015;Bazyler et al, 2014;Bell et al, 2014;Hart, Nimphius, et al, 2014), the relationship between asymmetry and CODS is not clear. Two investigations have noted reductions in CODS performance where an eccentric strength asymmetry is apparent (Chaouachi et al, 2012;Lockie et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Between-group analyses also indicated a 'large' and significant difference between median-split fast and slow performers. Whilst previous investigations have associated asymmetries in force-related parameters with impaired athletic performance (Bailey et al, 2013;Bailey et al, 2015;Bazyler et al, 2014;Bell et al, 2014;Hart, Nimphius, et al, 2014), the relationship between asymmetry and CODS is not clear. Two investigations have noted reductions in CODS performance where an eccentric strength asymmetry is apparent (Chaouachi et al, 2012;Lockie et al, 2012).…”
Section: Discussionmentioning
confidence: 97%
“…It is therefore conceivable that the observed association between asymmetry and CODS performance is purely indicative of participants' current athletic ability or training status. Indeed, Bazyler et al (2014) reported that asymmetries are likely to be greater in weaker individuals. Across a seven week bilateral training programme, Bazyler et al (2014) also noted that as strength increased there was a concomitant decrease in asymmetry in weaker individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With that in mind, a number of studies have reported how inter-limb asymmetries have changed following a targeted training intervention (4,8,11,12,19,30). This article will provide an overview of the available literature and suggest evidence-based methods to reduce interlimb differences.…”
Section: Introductionmentioning
confidence: 99%